Quality Care for Down Syndrome and Dementia - Tedder, Amanda (Journal of the American Academy of Special Education Professionals, 2012)
This article will give both examples and methods to use when providing services to individuals with a dual diagnosis of Down syndrome and Dementia. This is a prevalent issue that most care facilities are facing as the population with Down syndrome age. Staff training, schedule adjustments, living space adjustments and a new thought process regarding active treatment are essential for successful, quality care to take place.